Patterns of early life body mass index and childhood overweight and obesity status at eight years of age - Joseph M. Braun; Heidi J. Kalkwarf; George D. Papandonatos; Aimin Chen; Bruce P. Lanphear (BMC, 2018)
Abstract Background Excess weight gain in infancy and childhood is associated with increased risk of subsequent obesity. Identifying patterns of infancy and childhood weight gain associated with subsequent obesity or overweight status could help identify children at highest risk. Thus, we examined patterns of infancy and early childhood BMI in relation to mid-childhood overweight and obesity status. Methods In a prospective cohort of 215 children from Cincinnati, OH (born: 2003-2006), we measured weight and length or height at ages 4 weeks and 1, 2, 3, 4, 5, and 8 years. We calculated BMI z-scores using World Health Organization references. Using linear fixed effect models, we estimated mean BMI at each age and rates of change in BMI between ages 4 weeks and 5 years by children's overweight and obesity status at age 8 years, assessed with BMI z-scores or bioelectric impedance analysis (BIA). Results Children who became overweight (BMI, n = 51 and BIA, n = 37) or obese (BMI, n = 22 and BIA, n = 29) at age 8 years had greater BMI at all ages compared to normal weightchildren. Children who were overweight had similar rates of change in BMI as children who were lean. Children who were obese had greater gains in BMI between age 4 weeks and 5 years, with the most rapid gains in the first 2 years. Conclusions Results from this study of modest sample size, suggest that adiposity patterns in the first 5 years of life are related to subsequent childhood overweight and obesity risk.